SYSTEMATIC LITERATURE REVIEW (SLR): EXPLORASI PEMBAYARAN DIGITAL DI INDONESIA - Ihsani Mazelfi; Luciana Luthan; Zacky Marsa Ramadhan; Irvan Kurniawan T (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Digital payment systems in Indonesia have experienced rapid growth, driven by advancements in financial technology and supportive government policies. This study employs a Systematic Literature Review (SLR) approach to identify and synthesize key findings from existing research on digital payments in the Indonesian context. The review focuses on adoption trends, implementation challenges, and socio-economic impacts of digital payment platforms. The analysis reveals that factors such as digital literacy, user trust, regulatory frameworks, and technological infrastructure play critical roles in shaping the success of digital payment systems. This study contributes to future research by highlighting existing gaps, including the lack of longitudinal studies, limited exploration of user behavior in remote areas, and the need for multidisciplinary approaches to better understand the dynamics of the digital payment ecosystem. The findings are expected to serve as a foundation for researchers, policymakers, and industry stakeholders in designing more inclusive and sustainable digital payment strategies.Keywords: Digital Payment, Financial Technology (FinTech), Systematic Literature Review (SLR).